Does dexamethasone enhance control of acute cisplatin induced emesis by ondansetron?. Issue 6815 (7th December 1991) - Smyth, J F; Coleman, R E; Nicolson, M; Gallmeier, W M; Leonard, R C; Cornbleet, M A; Allan, S G; Upadhyaya, B K; Bruntsch, U
Abstract : OBJECTIVE–To determine the contribution of dexamethasone to the efficacy of the 5-hydroxytryptamine antagonist ondansetron in control of cisplatin induced nausea and vomiting. DESIGN–Randomised double blind crossover study. SETTING–Two cancer centres in teaching hospitals, one in the United Kingdom and the other in Germany. SUBJECTS–100 patients (53 men and 47 women) new to cisplatin chemotherapy, 84 of whom completed two consecutive courses of chemotherapy. INTERVENTIONS–Patients were given intravenous dexamethasone (20 mg) or physiological saline with intravenous ondansetron 8 mg before cisplatin, then ondansetron 1 mg/h for 24 hours. Oral ondansetron 8 mg was taken three times daily on days 2-6. MAIN OUTCOME MEASURES–Incidence of complete or major control of emesis (0-2 episodes in the 24 hours after chemotherapy). RESULTS–Complete or major control was obtained in 49 out of 71 (69%) of patients after receiving ondansetron plus dexamethasone compared with 40 out of 71 (56%) when they were given ondansetron alone (p = 0.012). This effect was most pronounced in the first 12 hours after chemotherapy. Patients receiving the combination also had significantly less nausea. Of the 53 patients who expressed a preference, 38 (72%) preferred the combination treatment (p = 0.002) to ondansetron alone. The effect of ondansetron on delayed emesis was less pronounced. CONCLUSIONS–Dexamethasone makes a significant contribution to the efficacy of ondansetron in the control of acute platinum induced emesis.